2011
DOI: 10.2176/nmc.51.45
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Fistula Involving the Inferior Petroclival Vein -Case Report-

Abstract: A 68-year-old man presented with an extremely rare extracranial arteriovenous fistula (AVF) involving the inferior petroclival vein (IPCV) with retrograde venous drainage into an ophthalmic vein through the anterior condylar confluence and inferior petrosal sinus manifesting as ocular symptoms. The AVF was successfully treated by selective transvenous embolization with platinum coils. AVF involving the IPCV should be recognized as a possible extracranial lesion manifesting as clinical symptoms similar to caver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 5 publications
(9 reference statements)
2
7
0
Order By: Relevance
“…5) based on the intraoperative findings combined with the detailed findings of multi-planer reconstruction (MPR) prepared by rotational angiography presented in a book written by Kiyosue et al 10) Pulsatile tinnitus is observed in many cases of DAVF of the ACC and that located around the hypoglossal canal, and symptoms, such as hypoglossal nerve palsy, have been reported, 5,6,11) but obstruction of the proximal side of the IPS may cause reflux into the CS, SOV, and SMCV and mainly induce ocular symptoms similar to those of DAVF of the CS, to which attention should be paid. 4,5,9,[11][12][13][14][15] The present case was similar to a previous case report in which blood flow refluxed in the IPS into the CS due to obstruction of the main venous drainage route, the proximal side of the IPS, and further reflux into the SOV mainly induced ocular symptoms similar to those of DAVF of the CS.…”
Section: Disclosure Statementsupporting
confidence: 89%
See 1 more Smart Citation
“…5) based on the intraoperative findings combined with the detailed findings of multi-planer reconstruction (MPR) prepared by rotational angiography presented in a book written by Kiyosue et al 10) Pulsatile tinnitus is observed in many cases of DAVF of the ACC and that located around the hypoglossal canal, and symptoms, such as hypoglossal nerve palsy, have been reported, 5,6,11) but obstruction of the proximal side of the IPS may cause reflux into the CS, SOV, and SMCV and mainly induce ocular symptoms similar to those of DAVF of the CS, to which attention should be paid. 4,5,9,[11][12][13][14][15] The present case was similar to a previous case report in which blood flow refluxed in the IPS into the CS due to obstruction of the main venous drainage route, the proximal side of the IPS, and further reflux into the SOV mainly induced ocular symptoms similar to those of DAVF of the CS.…”
Section: Disclosure Statementsupporting
confidence: 89%
“…To our knowledge, only one case of DAVF with a shunt in this region has previously been reported, indicating that this is a very rare shunting region. 9) On postoperative cone beam CT, the coil mass was demonstrated continuously from the extracranial IPCV to the intracranial IPS. The presence of a shunting region in the IPCV was confirmed (Fig.…”
Section: Disclosure Statementmentioning
confidence: 97%
“…A variety of devices, including detachable balloons, and transarterial or transvenous coils are used to occlude the fistula while attempting to maintain the patency of the vertebral artery 6–9. Our case report involved venous drainage into the anterior condylar confluence, which is the pathway for causing ocular symptoms, due to involvement of the inferior petrosal sinus10 11 In an extensive review, Spittau et al elegantly depicted the pathophysiology and treatment of hypoglossal canal dural arteriovenous fistulas, which may present with ocular symptoms similar to our case. Due to the complexity of the arterial–venous connections, a transjugular approach was the most commonly used treatment method, reserving transarterial treatment for lesions without venous access 12.…”
Section: Discussionsupporting
confidence: 61%
“…Endovascular surgery involves a catheter-based technique for embolization of the lumen of arteries feeding the DAVF, or directly into the vein draining the DAVF. The goal of treatment for intercavernous and carotid-cavernous sinus fistulas is to block the fistulous communications and thus decrease the hemodynamic burden in the cavernous sinus [11]. This can be accomplished either by occlusion of arterial feeders and proximal venous drainage through a transarterial approach or by retrograde transvenous occlusion of the sinus harboring the fistula.…”
Section: Discussionmentioning
confidence: 99%